2002
DOI: 10.1101/gr.229302
|View full text |Cite
|
Sign up to set email alerts
|

Alu-Containing Exons are Alternatively Spliced

Abstract: Alu repetitive elements are found in ∼1.4 million copies in the human genome, comprising more than one-tenth of it. Numerous studies describe exonizations of Alu elements, that is, splicing-mediated insertions of parts of Alu sequences into mature mRNAs. To study the connection between the exonization of Alu elements and alternative splicing, we used a database of ESTs and cDNAs aligned to the human genome. We compiled two exon sets, one of 1176 alternatively spliced internal exons, and another of 4151 constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
459
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(487 citation statements)
references
References 25 publications
24
459
1
3
Order By: Relevance
“…8,25 It may also lead to more subtle influences on the genes in which they insert, such as alterations in gene expression 26 and commonly through changes in splicing, a process termed Alu exonization. 27 However, because they also provide the most common source of dispersed sequence homologies throughout the genome, perhaps the biggest impact of Alu elements is their ability to contribute to genetic rearrangements. 25 The remarkable inhibition of Alu/Alu recombination by the accumulation of mismatches is critical to understanding how the high level of current Alu elements can be tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…8,25 It may also lead to more subtle influences on the genes in which they insert, such as alterations in gene expression 26 and commonly through changes in splicing, a process termed Alu exonization. 27 However, because they also provide the most common source of dispersed sequence homologies throughout the genome, perhaps the biggest impact of Alu elements is their ability to contribute to genetic rearrangements. 25 The remarkable inhibition of Alu/Alu recombination by the accumulation of mismatches is critical to understanding how the high level of current Alu elements can be tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…The Alu consensus sequence contains 9 potential 5' splice sites and 14 potential 3 splice sites [28,29], most of them being present on the minus strand. By genome-scale computational studies [29], Sorek and colleagues determined that 5.2 % of all identified alternative exons derive from Alu elements [29].…”
Section: Visions and Reflections (Minireview)mentioning
confidence: 99%
“…The Alu consensus sequence contains 9 potential 5' splice sites and 14 potential 3 splice sites [28,29], most of them being present on the minus strand. By genome-scale computational studies [29], Sorek and colleagues determined that 5.2 % of all identified alternative exons derive from Alu elements [29]. Sequence comparison of Alu exons revealed that not all potential splice sites were used at the same frequency [29]; the most favored sites were positions 275 and 279 used as 3 splice site and position 158 used as 5 splice site.…”
Section: Visions and Reflections (Minireview)mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In this scenario, a significant fraction of RNA molecules is ascribable to the Alu class of repetitive sequences that represents about one-tenth of the whole human genome. 4 Up to date, a long series of biological roles have been attributed to Alu short transcripts 5 including RNA editing, 6 alternative splicing regulation, 7 chromosomal recombination, 8 gene-expression regulation, 9 cell stress response, 10,11 putative miRNA targets. 12 Notably, the observation that the transcription of Alu elements is dependent on RNA polymerase (pol) III highlights a previously unexpected role in gene-expression regulation of this machinery that deserves further investigations.…”
Section: Introductionmentioning
confidence: 99%